Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/ng.1083
|View full text |Cite
|
Sign up to set email alerts
|

Compound inheritance of a low-frequency regulatory SNP and a rare null mutation in exon-junction complex subunit RBM8A causes TAR syndrome

Abstract: The exon-junction complex (EJC) performs essential RNA processing tasks1-5. Here, we describe the first human disorder, Thrombocytopenia with Absent Radii6 (TAR), caused by deficiency in one of the four EJC subunits. A compound inheritance mechanism of a rare null allele and one of two low-frequency SNPs in the regulatory regions of RBM8A, encoding the Y14 subunit of EJC, causes TAR. We found that this mechanism explained 53 of 55 cases (P<5×10−228) with the rare congenital malformation syndrome. Fifty-one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
358
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(379 citation statements)
references
References 36 publications
8
358
0
7
Order By: Relevance
“…Our approach also allowed us to segregate overlapping or adjacent DP-LCR-flanked fragments into distinct regions. For example, the thrombocytopenia-absent radius syndrome (TAR, MIM# 274000) region on 1q21 (Klopocki et al 2007;Albers et al 2012) and the 1q21.1 deletion/duplication syndrome region (MIM# 612474, 612475) (Brunetti-Pierri et al 2008;Mefford et al 2008) found in neuropsychiatric traits such as schizophrenia and autism (The International Schizophrenia Consortium 2008; Stefansson et al 2008), in addition to three adjacent regions on chromosome 2q12.2q13 (Liu et al 2012), were collapsed in previous reports but were separated by our analyses. Moreover, using the less stringent criterion for the length of flanking DP-LCRs copies, we have identified the STS deletions and duplications on Xp22.31 (MIM# 308100) (Hernández-Martín et al 1999;Liu et al 2011) that were not included in the analysis by Cooper et al (2011) and CNVs in Xq28 (El-Hattab et al 2011) that were not detected by the approach used by Liu et al (2012).…”
Section: Bioinformatic Genome-wide Analysesmentioning
confidence: 99%
“…Our approach also allowed us to segregate overlapping or adjacent DP-LCR-flanked fragments into distinct regions. For example, the thrombocytopenia-absent radius syndrome (TAR, MIM# 274000) region on 1q21 (Klopocki et al 2007;Albers et al 2012) and the 1q21.1 deletion/duplication syndrome region (MIM# 612474, 612475) (Brunetti-Pierri et al 2008;Mefford et al 2008) found in neuropsychiatric traits such as schizophrenia and autism (The International Schizophrenia Consortium 2008; Stefansson et al 2008), in addition to three adjacent regions on chromosome 2q12.2q13 (Liu et al 2012), were collapsed in previous reports but were separated by our analyses. Moreover, using the less stringent criterion for the length of flanking DP-LCRs copies, we have identified the STS deletions and duplications on Xp22.31 (MIM# 308100) (Hernández-Martín et al 1999;Liu et al 2011) that were not included in the analysis by Cooper et al (2011) and CNVs in Xq28 (El-Hattab et al 2011) that were not detected by the approach used by Liu et al (2012).…”
Section: Bioinformatic Genome-wide Analysesmentioning
confidence: 99%
“…Further evidence that EVI1 transcriptional regulation plays a key role in megakaryopoiesis comes from whole exome sequencing showing that a mutation creating an EVI1-binding site in the promoter of the RNA-binding motif protein 8A (RBM8A) gene underlies the thrombocytopenia with absent radii (TAR) syndrome [134]. In 80 % of a cohort of TAR patients, a single nucleotide polymorphism (SNP) was discovered in the 5′UTR of RBM8A.…”
Section: Evi1mentioning
confidence: 99%
“…65 However, the additional genetic factors do not have to be additional CNVs, and identifying such genetic variation may be difficult. There are a few examples where one of these CNVs acts as a recessive allele for certain phenotypes, pairing with variants on the non-deleted chromosome to cause disease, for example with RBM8A and 1q21.1 proximal microdeletions in thrombocytopenia-absent radius syndrome 66 or TBX6 and 16p11.2 proximal microdeletions in scoliosis, 67 but these seem to be rare, and additional genetic factors remain unknown in the majority of cases. It may therefore be challenging to determine if it would be useful to continue the diagnostic odyssey after CMA testing identifies a CNV risk factor, searching for additional contributing factors to disease.…”
Section: Discovery Of Microdeletion and Microduplication Syndromesmentioning
confidence: 99%